Selected papers from the 9th IFIP international conference on artificial intelligence applications and innovations (AIAI 2013) - Papadopoulos, Harris; Andreou, Andreas S.; Iliadis, Lazaros S.; Maglogiannis, Ilias G. (My University, 2014)
Segmentation of electronic dance music Tim Scarfe, Wouter M Koolen and Yuri Kalnishkan Adaptive evolutionary algorithm for a multi-objective VRP Andreas Konstantinidis, Savvas Pericleous and Christoforos Charalambos Unsupervised clustering and multi-optima evolutionary search Vassilis P Plagianakos Applying hard and fuzzy K-modes clustering for dynamic web recommendations Panayiotis Christodoulou, Marios Lestas and Andreas S Andreou A fuzzy cognitive map system to explore the repercussions of Greek PSI and bank recapitalization on the Cyprus economy Maria Papaioannou, Costas K Neocleous, Charalambos Papageorgiou and Christos N Schizas Fusion and gene and imaging information enhances derivation of robust composite disgnostic biomarkers in the case of melanoma Ioannis Valavanis, Ilias Maglogiannis and Aristotelis Chatziioannou Classification of osteoporosis clinical data using genetic clustering George C Anastassopoulos, Adam Adamopoulos, Georgios Drosos, Konstantinos Kazakos and Harris Papadopoulos Computational intelligence modeling and assessment of industrial noise: the case of wood manufacturing Vasiliki Dimou, Lazaros S Iliadis and Ilias Bougoudis
Keywords: Human engineering; International conference; Human computer interaction